PENERAPAN MODEL PEMBELAJARAN TIPE MAKE A MATCH BERBANTUAN MEDIA KONGKRET UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS DAN HASIL BELAJAR DI SEKOLAH DASAR - Ratnasari, Eka; Indarini, Endang (Pendidikan Dasar - Pascasarjana Universitas Negeri Jakarta, 2023)
The critical thinking skills of grade II at SD N Bringin 02 are still low. The low ability to think critically in class II causes low student learning outcomes. This happens because the lack of varied learning models used by teachers makes students bored and shy to ask questions. The weak critical thinking skills of students cause difficulty identifying and understanding in completing the tasks given. The purpose of this study was to apply the Make a Match learning model assisted by concrete media to improve the critical thinking skills and learning outcomes of grade II students at SD Bringin 02. In this class action research there are three stages, namely look, think, act. This research consists of two actions and involves class II which has 18 students. Data collection tools in this study are evaluation tests, observation, skills, documentation, and interviews. The results of research on action I, critical thinking skills showed an average of 64% while action II was 82%. The learning outcomes of action I students get a complete score of 44% and in action II have increased with a complete score of 89%.